Open Recruitment for Senior Leadership Positions in the Provincial Government of Papua South - Albert Gidion Peres Elmas; Wirman Syafri; Rizki Amalia (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
This study aims to identify, review, and analyze the Open Recruitment for the Filling of High-Level Leadership Positions Following the Establishment of the New Autonomous Region of Papua, the inhibiting factors, and the efforts made to overcome these obstacles. This study uses a qualitative approach with data collection techniques through interviews, observation, and documentation. The theory used in this study is Hugo Horta's theory (2014:22), namely Recruitment, Selection, Transparency, and Performance Assessment. The results of the study indicate that the implementation of open recruitment for the filling of Primary High Leadership Positions (JPT) in the South Papua Provincial Government has not been fully optimal. Success has only been seen in the selection and performance assessment dimensions, while in the recruitment and transparency dimensions there are still a number of significant weaknesses. Several factors hindering the implementation of this open recruitment include limited human resources; limited infrastructure and supporting facilities; and high political intervention and the dominance of local interests. To overcome these obstacles, strategic and systematic efforts are needed in line with applicable regulations, including through Improving the Quality and Quantity of Human Resources; Wider Socialization and Dissemination of Information; Overcoming Political Intervention and Group Interests; Utilization of Technology and Digitalization of the Recruitment Process.